2020
DOI: 10.3897/zookeys.973.55327
|View full text |Cite
|
Sign up to set email alerts
|

The Dacini fruit fly fauna of Sulawesi fits Lydekker’s line but also supports Wallacea as a biogeographic region (Diptera, Tephritidae)

Abstract: Although there is scientific consensus on most of the major biogeographic regions in the world, the demarcation of the area connecting Southeast Asia with Australia and Oceania remains debated. Two candidate boundaries potentially explain faunistic diversity patterns in the regions: Lydekker’s and Wallace’s lines. The islands in between both ‘lines’ are jointly termed Wallacea, with Sulawesi as the largest landmass. We surveyed Dacini fruit flies (Tephritidae: Dacinae) in Sulawesi between 2016 and 2019 using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The distribution of fruit flies in Western and Eastern Indonesia is influenced by the zoogeographic boundaries. Zoogeographic boundaries were initially created to show the striking faunal differences between the area and neighboring areas, known as the Wallace line and Lydekker line, between these lines is the Wallacea area [5][6][7]. According to zoogeography experts, the Wallacea region is referred to as a transition zone.…”
Section: The Distribution Area Of Fruit Flymentioning
confidence: 99%
“…The distribution of fruit flies in Western and Eastern Indonesia is influenced by the zoogeographic boundaries. Zoogeographic boundaries were initially created to show the striking faunal differences between the area and neighboring areas, known as the Wallace line and Lydekker line, between these lines is the Wallacea area [5][6][7]. According to zoogeography experts, the Wallacea region is referred to as a transition zone.…”
Section: The Distribution Area Of Fruit Flymentioning
confidence: 99%
“…As a tropical Island in the Wallacea region, Lombok has a wide variety of endemic flora and fauna with several types of habitats in tropical rainforests and orchards. According to Doorenweerd et al (2020), in any case, the geographic history of the islands has undoubtedly played a significant role in the evolution of the fauna.…”
Section: Introductionmentioning
confidence: 99%
“…However, these also have the potential to reduce the quality and quantity of fruit production. Doorenweerd et al (2020) suggested that the Dacini fruit flies (Tephritidae: Dacinae) are a tribe of 938 described exclusively Old World species.…”
Section: Introductionmentioning
confidence: 99%